Ryanodine Receptor Calcium Leak in Circulating B-Lymphocytes as a Biomarker in Heart Failure. Issue 11 (11th September 2018) - Kushnir, Alexander; Santulli, Gaetano; Reiken, Steven R.; Coromilas, Ellie; Godfrey, Sarah J.; Brunjes, Danielle L.; Colombo, Paolo C.; Yuzefpolskaya, Melana; Sokol, Seth I.; Kitsis, Richard N.; Marks, Andrew R.
Abstract : Background: Advances in congestive heart failure (CHF) management depend on biomarkers for monitoring disease progression and therapeutic response. During systole, intracellular Ca 2+ is released from the sarcoplasmic reticulum into the cytoplasm through type-2 ryanodine receptor/Ca 2+ release channels. In CHF, chronically elevated circulating catecholamine levels cause pathological remodeling of type-2 ryanodine receptor/Ca 2+ release channels resulting in diastolic sarcoplasmic reticulum Ca 2+ leak and decreased myocardial contractility. Similarly, skeletal muscle contraction requires sarcoplasmic reticulum Ca 2+ release through type-1 ryanodine receptors (RyR1), and chronically elevated catecholamine levels in CHF cause RyR1-mediated sarcoplasmic reticulum Ca 2+ leak, contributing to myopathy and weakness. Circulating B-lymphocytes express RyR1 and catecholamine-responsive signaling cascades, making them a potential surrogate for defects in intracellular Ca 2+ handling because of leaky RyR channels in CHF. Methods: Whole blood was collected from patients with CHF, CHF following left-ventricular assist device implant, and controls. Blood was also collected from mice with ischemic CHF, ischemic CHF+S107 (a drug that specifically reduces RyR channel Ca 2+ leak), and wild-type controls. Channel macromolecular complex was assessed by immunostaining RyR1 immunoprecipitated from lymphocyte-enriched preparations. RyR1 Ca 2+ leak was assessed using flow cytometry to measure Ca 2+ fluorescence in B-lymphocytes in the absence and presence of RyR1 agonists that empty RyR1 Ca 2+ stores within the endoplasmic reticulum. Results: Circulating B-lymphocytes from humans and mice with CHF exhibited remodeled RyR1 and decreased endoplasmic reticulum Ca 2+ stores, consistent with chronic intracellular Ca 2+ leak. This Ca 2+ leak correlated with circulating catecholamine levels. The intracellular Ca 2+ leak was significantly reduced in mice treated with the Rycal S107. Patients with CHF treated with left-ventricular assist devices exhibited a heterogeneous response. Conclusions: In CHF, B-lymphocytes exhibit remodeled leaky RyR1 channels and decreased endoplasmic reticulum Ca 2+ stores consistent with chronic intracellular Ca 2+ leak. RyR1-mediated Ca 2+ leak in B-lymphocytes assessed using flow cytometry provides a surrogate measure of intracellular Ca 2+ handling and systemic sympathetic burden, presenting a novel biomarker for monitoring response to pharmacological and mechanical CHF therapy. Abstract : Supplemental Digital Content is available in the text.